Study on the influence of material hardness on the performance of V-shaped non-pneumatic tyres - Sichen Gao; Yuan Yu; Mingjiao Sun; Weimin Yang; Zhenchuan Song; Yangjun Zheng; Jiangming Yuan; Zhibin Shuai; Zhiwei Jiao (Heliyon)
Material selection is a crucial factor in the design of non-pneumatic tyres (NPT). Most NPTs are integrally manufactured using polyurethane materials for the supports, the inner ring, and the outer ring. It is evident that designing different components with varying material hardness will have distinct impacts on NPT performance. To study the influence of material hardness on the performance of V-shaped non-pneumatic tyres (VS-NPT), we developed finite element models of VS-NPTs with different TPU materials. To validate the finite element models, we manufactured tyres with three different hardness levels and conducted performance tests. Based on this model, a design concept is proposed where different components use materials with varying hardness levels. To elucidate how material hardness affects VS-NPT performance, the Taguchi method was used for analysis. The results reveal that increased material hardness leads to higher triaxial forces and triaxial stiffness in integrally designed VS-NPTs. Regardless of variations in the structural parameters of existing VS-NPTs, the spoke material has a significant impact on triaxial stiffness and contact area. When the spoke thickness exceeds 7.3 mm, the tread material predominantly affects the contact area.